Examining the Role of Coaching, Mentoring, and Work Experience in Employee Performance at the Madya Dua Tax Service Office, Surabaya - Afrian, Nurul; Purwanto, Purwanto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the influence of coaching, mentoring, and professional experience on the performance of employees at KPP Madya Dua Surabaya, a public tax office operating under the Directorate General of Taxes. Adopting a quantitative explanatory research design, the study involved 97 civil servants who completed structured questionnaires, with data analyzed using multiple linear regression techniques. Findings indicate that each factor coaching, mentoring, and work experience independently enhances employee performance, while their combined effect produces the most substantial improvement. Coaching supports employees in developing creative solutions, adaptive problem-solving abilities, and innovative task management strategies. Mentoring enables knowledge transfer, skill refinement, leadership development, and fosters engagement through guidance and professional modeling. Work experience allows employees to translate accumulated knowledge into practical performance, building competence and efficiency over time. Descriptive insights further highlight employees’ positive perception of developmental interventions, emphasizing that structured guidance, role modeling, and hands-on experience are key to professional growth. The results underscore that employee performance is optimally achieved through a holistic approach integrating supervisory support, mentoring relationships, and practical experience rather than isolated interventions. Based on these findings, it is recommended that KPP Madya Dua Surabaya implement systematic coaching frameworks, clearly defined mentoring objectives, and strategic staff placements that capitalize on employees’ existing expertise. By doing so, the organization can enhance employee productivity, ensure consistent achievement of institutional goals, and strengthen overall human resource capacity in public sector tax administration.